Evaluation of mid-term clinical and radiologic outcomes after open reduction and internal fixation of Lisfranc fracture-dislocations: A case series - Uzun, Erdal; Misir, Abdulhamit; Bilge Kizkapan, Turan; Ozcamdalli, Mustafa; Arat, Feridun (Annals of Medical Research, 2021)
Aim: To evaluate the mid-term clinical and radiologic outcomes after surgical treatment of Lisfranc fracture dislocations. Material and Methods: Twenty unstable Lisfranc joint fracture dislocation patients treated with open reduction and internal fixation (ORIF) were evaluated retrospectively. Kirschner wire, screw or a combination of Kirschner wire (K-wire) and screw fixation were used in the internal fixation. American Orthopedic Foot and Ankle Society - Midfoot Scale (AOFAS-MS) score, Maryland foot score, Visual Analog Scale (VAS) and SF-36 survey were obtained at the last follow-up. Nonunion, implant failure, reduction quality and the degree of posttraumatic arthritis were evaluated on the AP, lateral and oblique foot radiographs. The outcome measures included the Kellgren-Lawrence grading of osteoarthritis and the Stein’s criteria for anatomic reduction.Results: The mean follow-up duration was 3.7±1.4 years. Mean AOFAS and Maryland foot scores were 75.3±1.72 and 71.8±2.3, respectively. Nonunion was developed in three patients (15%) and posttraumatic arthritis was observed in 7 patients (35%).Conclusion: Good overall clinical and radiologic outcomes can be obtained in the mid-term follow up after open reduction and internal fixation of Lisfranc fracture dislocations. However, higher-energy injuries such as open fracture-dislocations and Myerson type C2 injuries have poor outcomes.Keywords: Fracture dislocation; lisfranc; open reduction; arthritis.
Keywords: Fracture dislocation; lisfranc; open reduction; arthritis.